Marketing y Gestión Responsable en Ecuador. Un análisis desde la perspectiva del neologismo de la posverdad - Avellán Herrera, Nilda Alexandra (2023)
The purpose of this work was to analyze the behavior of marketing and responsible management in Ecuador; as a reflection of the importance of contrasting with facts the information received through marketing where the post-truth discourse may be implicit, for which greenwashing practices are exposed. A descriptive level of research was used and as a research technique for the collection of data and relevant information, the bibliographic or documentary that supports the theoretical review and the results presented. As a main conclusion, it was determined that in the business world the post-truth discourse can be present when communicating through misleading advertising about the social and environmental management that a company or organization supposedly carries out, this practice being known as greenwashing.